Cannabis policy in The Netherlands: Rationale and design of an experiment with a controlled legal ('closed') cannabis supply chain. (March 2023) - Knottnerus, J. André; Blom, Tom; van Eerden, Sanne; Mans, Jan H.H.; Mheen, Dike van de; de Neeling, J.Nico D.; Schelfhout, David C.L.; Seidell, Jaap C.; van Wijk, Albert H.; van Wingerde, C.G. (Karin); Brink, Wim van den
Abstract: Since the Dutch tolerance policy, allowing the purchase of cannabis in 'coffeeshops', is associated with problems of public order and safety as well as health risks, there has been a long debate about legalisation of cannabis production and supply. It was therefore decided to conduct an experiment with a controlled legal ('closed') cannabis supply chain for recreational use. This is of international relevance in view of the current illegal cannabis exports from the Netherlands, the importance of sharing knowledge about the effectiveness of cannabis policies, and the accumulation of evidence needed to evaluate and update international treaties. Here we describe and discuss the background, general approach and design of the experiment. An independent expert committee elaborated how the closed chain will operate and be evaluated, based on the experience with the medicinal cannabis chain, and round table discussions with stakeholders (mayors, coffeeshop owners, cannabis consumers, growers, regulators, scientists, and addiction experts). Ten trusted cannabis growers are contracted to produce and supply cannabis to the coffeeshops in intervention municipalities, with product quality control, law enforcement against criminal interference, and preventive efforts to reduce health risks being implemented. No changes will be made in the cannabis supply to the coffeeshops in participating control municipalities. A process evaluation will assess whether the chain from production to sale in the intervention municipalities was really closed. In a quasi-experimental study comparing intervention and control municipalities, the chain's effects on public health, cannabis-related crime, safety and public nuisance will be estimated. The fieldwork period is expected to start early 2024 and will take four years, including reporting to the government and parliament. These will then decide whether and what further steps towards legalisation of the production and supply of cannabis will be taken.